When Fiction Is Just as Real as Fact: No Differences in Reading Behavior between Stories Believed to be Based on True or Fictional Events - Hartung, Franziska; Withers, Peter; Hagoort, Peter; Willems, Roel M. (Frontiers in Psychology, 2017)
Experiments have shown that compared to fictional texts, readers read factual texts faster and have better memory for described situations. Reading fictional texts on the other hand seems to improve memory for exact wordings and expressions. Most of these studies used a ‘newspaper’ versus ‘literature’ comparison. In the present study, we investigated the effect of reader’s expectation to whether information is true or fictional with a subtler manipulation by labelling short stories as either based on true or fictional events. In addition, we tested whether narrative perspective or individual preference in perspective taking affects reading true or fictional stories differently. In an online experiment, participants (final N=1742) read one story which was introduced as based on true events or as fictional (factor fictionality). The story could be narrated in either 1st or 3rd person perspective (factor perspective). We measured immersion in and appreciation of the story, perspective taking, as well as memory for events. We found no evidence that knowing a story is fictional or based on true events influences reading behavior or experiential aspects of reading. We suggest that it is not whether a story is true or fictional, but rather expectations towards certain reading situations (e.g. reading newspaper or literature) which affect behavior by activating appropriate reading goals. Results further confirm that narrative perspective partially influences perspective taking and experiential aspects of reading.